Analysis of Business Legality and Halal Certification at Bebek Sinjay Food Stall Company, Bangkalan, Madura - Deviana Putri Septia Ningrum (Al-Fadilah: Islamic Economics Journal, 2025)
Bebek Sinjay restaurant is one of the MSMEs that is already familiar in Indonesia, especially Madura. To find out consumer attitudes towards halal certification at Bebek Sinjay Restaurant, a study regarding consumer attitude analysis is needed. The purpose of this research is to analyze consumer attitudes towards halal certification at the Bebek Sinjay restaurant. This research focused on consumers at BebekSinjay Restaurant who were selected purposively. This research was carried out using a qualitative approach with the data analysis method used in this research being Multi and to find out how important flexibility is in this company, considering that many businesses/companies do not yet have a business license. Company register is a list of official records maintained in accordance with or based on the provisions of this law and/or its implementing regulations, and contains matters that must be registered by every company and approved by an authorized official from the company registration office.